Penerapan Metode Profile Matching Dalam Evaluasi Kinerja Karyawan - Raditya Rimbawan Oprasto (CHAIN: Journal of Computer Technology, Computer Engineering, and Informatics, 2024)
Employee performance is an evaluation of individual contributions and achievements in achieving goals and work standards set by the company. Employee performance evaluation covers various aspects, including productivity, quality of work, compliance with company policies, as well as the ability to collaborate and adapt to the work team. One of the problems that occurs is the lack of clarity in determining evaluation criteria that are appropriate and relevant to organizational goals. Appraiser objectivity can arise from subjective preferences or unfair appraisals of appraisers towards certain employees, and lack of consistency in the application of evaluation standards and the unavailability of adequate data can also hinder the effective performance evaluation process. The profile matching method in employee performance evaluation involves comparing an individual's performance profile with an expected or desired profile for a particular position or role in the organization. The purpose of this study is to apply the profile matching method in evaluating employee performance so that it will produce the best performance recommendations from existing employees. The profile matching method is not only an employee performance evaluation tool, but also a powerful management strategy to increase productivity, motivation, and job satisfaction in the workplace. The results of employee performance evaluation using the profile matching method recommend Rina as the employee with the best performance because she gets a total score of 4.5175 and gets 1st place.